Pengembangan Nilai-nilai Filosofis Pepali sebagai Strategi Self-Monitoring bagi Siswa Kelas VIII SMP Baitul Arqom - Purnamasari, Yunita; Isriyah, Mudafiatun; Fauziyah, Nailul (SENTRI: Jurnal Riset Ilmiah, 2025)
This research is motivated by the importance of strengthening character education through the integration of local wisdom values in learning. The values of Pepali Ki Ageng Selo contain moral teachings such as honesty, responsibility, and self-control that are relevant to the formation of students' character. This study aims to develop and test the effectiveness of the self-monitoring strategy based on the values of Pepali Ki Ageng Selo in increasing self-awareness, behavior control, and internalizing moral values of grade VIII students of Baitul Arqom Junior High School. The research method uses a Research and Development (R&D) approach with data collection techniques through questionnaires, in-depth interviews, and participatory observation. Quantitative results showed an increase in the average score in the aspect of self-awareness from 60.3 to 74.2, behavior control from 57.9 to 72.5, and internalization of Pepali value from 55.8 to 71.3. Meanwhile, qualitative results showed positive changes in students' behavior who were more reflective, able to control themselves, and apply moral values in daily life. These findings show that Pepali's value-based self-monitoring strategy is effective in strengthening character education based on local culture.